ETNOGRAFI PEMIRSA TELEVISI DI YOGYAKARTA : KISAH DUA KELUARGA - , RENY TRIWARDANI, Dr. Nicolaas Warouw ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis describes the results of studies that investigated the television watching activities according to the experiences of two families in Yogyakarta and how contextual aspects which were involved to negotiate in the interaction of daily media. This thesis does not intend to measure and find out a specific effect of media usage on family informants, but it merely gives a description of watching television as a cultural practice. The study was also conducted as a counter-argument from the tradition of media effects research on passive audience. For this purpose, the researcher used ethnographic methods which not only involve researcher in family informantsâ daily but also conduct interviews to complete the knowledge of researchers about the dynamics of watching behavior in the family. Based on the ethnographic studies which were done, it was found that watching behavior in the family is not monotonous and passive. They do not really give full attention to watch television. Watching television is only one of the existence cultural practices and not the only practices in their daily life. By understanding watching television experiences in these families, based on the usage of television media and the responses of informants toward the television, this study showed the contextual aspects which were involved to negotiate as a cultural resource in understanding of television.